The desiring tongue. Disgust and good taste in La lengua del malón by Guillermo Saccomanno (Anclajes, 2024)
The memory of peoples is built upon the clash between different discourses and sectors which strive to occupy a privileged place in this collective symbolic space. Other discourses work deconstructing those hegemonic narratives, reporting what they have left aside and giving voice to those who have been systematically silenced. This work tries to account for the way in which La lengua del malón, by Guillermo Saccomanno, builds itself as a counter-discourse, which allows to discern the position of some social sectors in reference to discourses and devices that determine what is adequate, moral, vulgar, tasteful, normal. To the same extent, this paper attempts to exhibit those sectors’s complicity in keeping hierarchies, categories and institutions, which are conservative, oppressive and repressive, together with their alliances with those who interrupted democratic and popular processes. The novel is based on the coup d'etat which overthrew Perón's government in 1955, and it hints the continuing relationship with other tragic moments of the Argentinian history: the extermination of native peoples and the dictatorship that started in 1976. La lengua del malón is built as a narrative of abjection suffered by those who fail to answer those hegemonic parameters supporting not only the official history, but also the society.
Keywords: La lengua del malón; Guillermo Saccomanno; novel; Argentinian literature; 20th Century.